2014
DOI: 10.1159/000362687
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signalling in Pericytes

Abstract: Recent advances in pericyte research have contributed to our understanding of the physiology and pathophysiology of microvessels. The microvasculature consists of arteriolar and venular networks located upstream and downstream of the capillaries. Arterioles are surrounded by a monolayer of spindle-shaped myocytes, while terminal branches of precapillary arterioles, capillaries and all sections of postcapillary venules are encircled by a monolayer of morphologically diverse pericytes. There are physiological di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 164 publications
2
36
0
Order By: Relevance
“…Capillary pericytes are often non‐contractile and do not express α‐smooth muscle actin (α‐SMA) (Borysova et al . ; Burdyga & Borysova, ; Hill et al . ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Capillary pericytes are often non‐contractile and do not express α‐smooth muscle actin (α‐SMA) (Borysova et al . ; Burdyga & Borysova, ; Hill et al . ).…”
Section: Introductionmentioning
confidence: 98%
“…Arterioles or venules are surrounded by contractile smooth muscle cells (SMCs), whereas capillaries and pre-and post-capillary microvessels are covered by morphologically distinct pericytes. Capillary pericytes are often non-contractile and do not express α-smooth muscle actin (α-SMA) (Borysova et al 2013;Burdyga & Borysova, 2014;Hill et al 2015). Nevertheless, capillary pericytes in several vascular beds of the CNS play an active role in regulating capillary diameter and blood flow (Peppiatt et al 2006;Femández-Klett et al 2010;Hall et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, it was reported that L-type VDCCs have a minimal role in establishing the basal Ca 2+ concentration of capillary pericytes, while L-type VDCCs in mural cells in the proximal retinal microvasculature exhibit significant basal activity [29]. Thus, in terms of the involvement of L-type VDCCs, the properties of Ca 2+ transients in the microvasculature seem to vary amongst vascular beds or may exhibit regional differences even within a microvascular network (see also [30]). Importantly, we found that the near synchronous mural cell Ca 2+ transients in the myenteric microvasculature were abolished by blockers of T-type VDCCs used at concentrations comparable to those used to completely block Ca v 3.1 T-type VDCCs [20,31].…”
Section: Generation Of Synchronous Spontaneous Ca 2+ Transients In Mymentioning
confidence: 99%
“…It is well established that pericyte-containing capillaries are important functional units involved in regulating tissue blood supply [1]. When the sensory input increases blood flow in vivo , capillaries dilate before the arterioles [2] and account for up to 84% of the increase in blood flow.…”
Section: Introductionmentioning
confidence: 99%